2019
DOI: 10.3390/ijms20051217
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Anti-proliferative Activity and Mechanism of Action of Anemone nemorosa

Abstract: Anemone nemorosa is part of the Ranunculaceae genus Anemone (order Ranunculales) which comprises more than 150 species. Various parts of the plant have been used for the treatment of numerous medical conditions such as headaches, tertian agues, rheumatic gout, leprosy, lethargy, eye inflammation as well as malignant and corroding ulcers. The Anemone plants have been found to contain various medicinal compounds with anti-cancer, immunomodulatory, anti-inflammatory, anti-oxidant and anti-microbial activities. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 27 publications
(31 reference statements)
0
9
0
1
Order By: Relevance
“…Cells were maintained in 10 cm culture dishes in complete DMEM low glucose (Vero, MRHF and MeWo), EMEM (HepG2), or RPMI 1640 (HeLa) supplemented with 10% foetal bovine serum (FBS) (Biowest) and incubated at 37 °C in a humidified incubator with 5% CO 2 . Additional supplementation, in the form of MEM Non-Essential Amino Acids at 1X with the stock concentration (HyClone), was required for HepG2 cells [34]. Cells exceeding 80% confluency were never used for maintenance and seeding of 96-well plates.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cells were maintained in 10 cm culture dishes in complete DMEM low glucose (Vero, MRHF and MeWo), EMEM (HepG2), or RPMI 1640 (HeLa) supplemented with 10% foetal bovine serum (FBS) (Biowest) and incubated at 37 °C in a humidified incubator with 5% CO 2 . Additional supplementation, in the form of MEM Non-Essential Amino Acids at 1X with the stock concentration (HyClone), was required for HepG2 cells [34]. Cells exceeding 80% confluency were never used for maintenance and seeding of 96-well plates.…”
Section: Methodsmentioning
confidence: 99%
“…The ImageXpress Micro XLS Widefield High-Content Analysis System (Molecular Devices ® , San Jose, CA, USA) together with the MetaXpress ® High-Content Image Acquisition and Analysis Software was used to acquire and analyse all images, for all experiments [34]. All assays were conducted in 96-well plates of which the area of one well was approximately 34.21 mm 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Anemonoides nemorosa and Tecomella undulata are used in traditional medicines to treat gout. Studies showed that Aqueous extracts of A. nemorosa can induce cell cycle arrest and apoptosis by regulating mitochondrial function ( 154 ). Tecomella undulata induces apoptosis in tumor cells by promoting Fas, Fas-associated death domain, caspase3/7/8, and DNA fragmentation ( 155 ).…”
Section: Apoptosismentioning
confidence: 99%
“…A group of researchers also studied the efficiency of juncusol isolated from Juncus inflexu by introducing them in the cells of HeLa, CaSki as well as SiHa cells and found that the compound exhibited the potential of inducing apoptosis and inhibiting cell proliferation [33]. By analysing the cell cycle it was also concluded that G2/M as well as sub G1 cell populations were increased when treated with juncusol [58][59][60][61][62][63][64][65]. Moreover, this compound when added to HeLa cells was able to increase the activity of caspase-3, -8, as well as -9 which further suggest that it can also induce apoptosis.…”
Section: Various Natural Compoundsmentioning
confidence: 99%